Audit Quality Framework’s Input Factors: An Islamic Perspective - Mohammed Ayedh, Abdullah; A.H., Fatima (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
Abstract The International Federation of Accountants issued the Audit Quality Framework (AQF) in 2014. This framework portrays the factors that enable a quality audit as a systematic process. This paper provides an Islamic perspective to the AQF, specifically on the input factors. Since the analysis is from an Islamic viewpoint, primary Islamic sources are referred to. Moreover, a diagram of the main characteristics is included for simplification. The analysis reveals that although the AQF is reasonably comprehensive, there are some other considerations that Muslim auditors must make in performing an audit of quality, for example their intention. Then, the qualities of ‘morality’ and ‘proficiency’, have augmented significance compared to the original AQF. The proposed model could be useful to regulators and audit firms in Muslim countries. Also, these factors should be considered by Muslim auditors and practiced. Furthermore, researchers could test the model empirically in future.